KAJIAN PENGEMBANGAN BAHAN AJAR MELALUI ANALISIS KI DAN KD DALAM MATA PELAJARAN SKI PADA MADRASAH TSANAWIYAH (MTs) - Muaripin Muaripin (Tatar Pasundan: Jurnal Diklat Keagamaan, 2018)
The purpose of this paper is to know how far the understanding of training participants on the development of teaching materials on the training of teacher competence improvement History of Islamic culture MTs in the Ministry of Religious Affairs of West Java Province. The method used is descriptive analysis because this method describes in general about the ability of training participants about the development of teaching materials in text form on the subjects of Islamic Culture History MTs through the analysis of Core Competence and Basic Competence. The results of the study that the authors do that that the preparation of teaching materials in text form on the subjects of History of Islamic Culture MTs is needed and help teachers and simplify the process of teaching and learning in the classroom and can improve the quality of learning. Even teaching materials in text form can be developed as teaching materials based on e-learning. In developing teaching materials in text form, teachers should perform KI and KD analysis first.  Key words: development, teaching materials, KI and KD